Looking at ourselves: Lessons about the operations management field learned from our top journals. Issue 3 (29th January 2020) - Babbar, Sunil; Koufteros, Xenophon; Bendoly, Elliot; Behara, Ravi; Metters, Richard; Boyer, Kenneth
Abstract: We focus here on questions regarding the craft of producing operations management (OM) research manuscripts. Are the journals we publish in too siloed, with regard to participating authors and institutions? Likewise, are the OM departments we work in too intellectually siloed by virtue of journal choice—are there too many like minds? In light of who publishes in our journals and who we coauthor with, is our field "global enough" or is North America weighing too heavily? We also strive to answer a question faced by many OM departments: should highly published faculty be hired from other schools? How do such highly published authors influence those around them? We arrive at partial answers to these questions by exploring an extensive history of publication data from four journals: Journal of Operations Management, Production and Operations Management, Manufacturing and Service Operations Management, and Management Science .